2012
DOI: 10.2174/1874065001206010001
|View full text |Cite
|
Sign up to set email alerts
|

Capillary Gas Chromatography-Mass Spectrometry (CGC-MS) Analysis and Antioxidant Activities of Phenolic and Components of Guarana and Derivatives

Abstract: Abstract:The GC-MS analysis of phenolic compounds present in guarana (Paullinia cupana), an important product of the Amazonian forest consumed in supplements or in soft drinks has been the subject of study. The therapeutic properties and possible protective effects reported for guarana and derivative products could be associated with the antioxidant activity of their phenolics content. The purpose of this study is i) to provide molecular structural information about the composition of guarana in phenolics; ii)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Tor et al (1996) when determining gallic acid and pirrogalol in biological matrices by gas chromatography coupled to mass spectrometry (GC/MS) derivatized the sample prior to injection. The column used was a J & W Scientific 15 m £ 0.53 mm £ 0.1 mm DB-1, with helium gas drag and flow rate of 7 mL/min, operating at 60 C and oven temperature gradient system up to 275 C. Sample derivatization was also adopted by Kuskoski et al (2012) in analyzing phenolic compounds by GC/MS ion trap in guarana (Paullinia cupana). To this end, the research used a fused silica capillary column (Phenomenex Zebron ZB-5ms 30 m £ 0.25 mm £ 0.25 mm), with a temperature of 300 C of injection and helium gas drag with flow rate of 1 mL/min.…”
Section: Gas Chromatography (Gc)mentioning
confidence: 99%
“…Tor et al (1996) when determining gallic acid and pirrogalol in biological matrices by gas chromatography coupled to mass spectrometry (GC/MS) derivatized the sample prior to injection. The column used was a J & W Scientific 15 m £ 0.53 mm £ 0.1 mm DB-1, with helium gas drag and flow rate of 7 mL/min, operating at 60 C and oven temperature gradient system up to 275 C. Sample derivatization was also adopted by Kuskoski et al (2012) in analyzing phenolic compounds by GC/MS ion trap in guarana (Paullinia cupana). To this end, the research used a fused silica capillary column (Phenomenex Zebron ZB-5ms 30 m £ 0.25 mm £ 0.25 mm), with a temperature of 300 C of injection and helium gas drag with flow rate of 1 mL/min.…”
Section: Gas Chromatography (Gc)mentioning
confidence: 99%
“…The guarana seed is a vital asset in promoting wellness and health revitalization, boasting a chemical profile rich in caffeine (2.5% to 6.0%), phenolic compounds, and essential macro- and microelements [ 3 6 ]. Moderate consumption of guarana has been associated with several health benefits such as the prevention of cardiovascular and neurodegenerative diseases [ 7 , 8 ], antioxidant, antimicrobial, and anti-inflammatory activity [ 9 , 10 ], as well as protection against DNA damage and antitumor action [ 11 , 12 ]. In addition, recent studies have further highlighted guarana's potential to enhance human cognitive performance [ 13 ] and positively affect energy metabolism in animal models, suggesting promising avenues for addressing obesity-related conditions [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…A comprehensive literature survey revealed that some methods are available for the analysis of gallic in other plant samples, that include liquid chromatography methods, capillary electrophoresis methods, capillary gas chromatography method hyphenated with mass spectrometry and liquid chromatography combined with tandem mass spectrometry (Deodhar et al, 2012;Deshmukh and Prabhu, 2011;Kuskoski et al, 2012;Wang et al, 2013;Yue et al, 2006). But, no simple and validated high performance thin layer chromatography (HPTLC) method was reported for gallic acid estimation in H. salicifolia.…”
Section: Introductionmentioning
confidence: 99%